Epicardial progenitor cells in cardiac regeneration and neovascularisation. - Smart, N; Dubé, K; Riley, P (2013)
While cardiovascular diseases remain the major worldwide cause of mortality and morbidity, there is an urgent need to tackle the clinical and economic burden of heart failure. Since the mammalian heart is unable to adequately regenerate beyond early postnatal stages, individuals surviving acute myocardial infarction are at risk of heart failure. Understanding the embryonic mechanisms of vasculogenesis and cardiogenesis, as well as the mechanisms retained for regeneration in species such as the zebrafish, will inform on strategies for human myocardial repair. Due to their fundamental role in heart development, epicardium-derived cells (EPDCs) have emerged as a population with potential to restore myocardium and coronary vasculature. The ability to revive ordinarily dormant EPDCs lies in the identification of key molecular cues used in the embryo to orchestrate cardiovascular development. One such stimulatory factor, Thymosin β4 (Tβ4), restores the quiescent adult epicardium to its pluripotent embryonic state. Tβ4 treatment of infarcted hearts induces dramatic EPDC proliferation and formation of a network of perfused, functional vessels to enhance blood flow to the ischaemic myocardium. Moreover, Tβ4 facilitates an epicardial contribution of mature de novo cardiomyocytes, structurally and functionally coupled with resident myocardium, which may contribute towards the functional improvement of Tβ4-treated hearts post-MI.